2005
DOI: 10.2133/dmpk.20.324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Levothyroxine Treatment Decreases the Oral Bioavailability of Cyclosporin A by Inducing P-glycoprotein in Small Intestine

Abstract: Summary:We have noticed that the trough level of blood concentration of cyclosporin A (CyA) tends to be lower in patients receiving long-term oral levothyroxine (LTX) than in patients not receiving LTX. We conˆrmed this clinical observation in experiments using Wistar rats orally given LTX (8 mg W kg) or saline (control) for 3 weeks, followed by CyA (10 mg W kg). The LTX treatment had little eŠect on the blood concentrations of CyA after i.v. administration, whereas they were decreased signiˆcantly after p.o. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 20 publications
1
24
0
Order By: Relevance
“…An archetypal example is the natural product cyclosporine A (CSA), a cyclic undecapeptide immunosuppressant that is passively permeable and has an oral bioavailability of 29% [22]. While many other cyclic peptide natural products have structures that also suggest bioavailability [21], there have been no reports that systematically examine the passive membrane permeabilities of other naturally occurring cyclic peptides.…”
mentioning
confidence: 99%
“…An archetypal example is the natural product cyclosporine A (CSA), a cyclic undecapeptide immunosuppressant that is passively permeable and has an oral bioavailability of 29% [22]. While many other cyclic peptide natural products have structures that also suggest bioavailability [21], there have been no reports that systematically examine the passive membrane permeabilities of other naturally occurring cyclic peptides.…”
mentioning
confidence: 99%
“…8 Significant decrease of oral bioavailability of cyclosporine A, by P-gp induction in intestine, was observed in an experimental rat model during levothyroxine cotreatment. 12 This mechanism was considered responsible for the significantly lower cyclosporine C min observed among 10 patients who were on long-term cotreatment with cyclosporine and 100 mcg daily oral levothyroxine, as compared with values from 30 patients who took only cyclosporine. 12 Overall, these data suggest that the long-term levothyroxine replacement therapy might have increased CL/F of linezolid in our hypothyroid patient.…”
mentioning
confidence: 99%
“…12 This mechanism was considered responsible for the significantly lower cyclosporine C min observed among 10 patients who were on long-term cotreatment with cyclosporine and 100 mcg daily oral levothyroxine, as compared with values from 30 patients who took only cyclosporine. 12 Overall, these data suggest that the long-term levothyroxine replacement therapy might have increased CL/F of linezolid in our hypothyroid patient. Clinicians should be aware that patients who receive standard oral dosages of linezolid while on replacement therapy with levothyroxine might experience linezolid underexposure and that TDM may be valuable in these occasions.…”
mentioning
confidence: 99%
“…Therefore, it is likely that the kinetics of diazepam are not affected with hyperthyroidism. As for Pgp substrates, it was recently reported that long-term levothyroxine treatment decreased the oral bioavailability of cyclosporine A (29). Thus, it is reasonable to assume that the changes in Pgp expression in the human gut affect at least in part the alteration of the blood concentration of digoxin.…”
Section: Discussionmentioning
confidence: 99%